(untitled) (World Economics and Finance Bulletin, 2023)
The current study aims to show the impact of accounting information on the market value of shares in companies listed on the Iraq Stock Exchange. Using a set of measures represented by (changes in book value per share, changes in return on assets, changes in asset turnover, changes in operating cash flow per share, and changes in earnings per share) and the market value of companies’ shares through the share price in the market, and to achieve the goal of this study, we selected a sample of 25 companies for four sectors that included services, industry, hotels and agriculture for the financial period (2014-2020), where the hypotheses were tested through the statistical program (STATA) at a level of significance (0.05), and the results of the study indicate a relationship. Statistically significant between the changes in the book value of each share and the changes in the price of each share of the shares of companies listed on the Iraq Stock Exchange, which means that there is an impact of accounting information on the market value of shares, and there is no statistically significant relationship between changes in return on assets, changes in asset turnover, changes in operating cash flow per share, and changes in earnings per share on the price of they are in the market. As for the restrictions, they included the lack of timely accounting information for companies due to the political and economic conditions of the country, and the crises it is going through, the most important of which was the ISIS and Corona crisis, which led to the majority of companies disclosing their financial reports in separate years, the most important recommendations that came in our study on companies The need to provide accounting information in a timely manner by disclosing it in the financial reports listed on the stock market because this will enhance investor confidence, which leads to Attracting them to further investment, as well as the availability of timely information helps in the use of other financial indicators and the expansion of this study